Who is saying what? An investigation into Word-of-mouth Communication at the British Council Singapore Teaching Centre - Gibbings, James Michael (2010)
Prospects considering a service purchase may seek recommendations or opinions from consumers who have previous experience of the provider. Word-of-mouth communication (WOM) can play a key part in the purchase decision-making process, and is thought to have grown in influence as consumers have become more wary of corporate information sources.